Dissolution of coals near critical conditions - Pehlivan, D; Gurkahraman, M; Pamuk, V (Marcel Dekker Inc, 1996)
Two lignites and one bituminous coal were extracted with benzene, toluene and pyridine at both sub and overcritical conditions in a specially designed experimental system which enabled easy solid-liquid separation. Extract yields increased somewhat at overcritical conditions due to more thermal decomposition. The differences between the power of the solvents were not apparent for the lignites, whereas the solubility in pyridine of the bituminous coal was very much higher than those in benzene and toluene. The amounts of oils, asphaltenes and preasphaltenes in the extracts depended on the type of coal and the solvent.
Keywords: Extraction